2021
DOI: 10.31083/j.ceog.2021.01.2124
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of obstetric patients requiring ICU admission: a 5-year retrospective review

Abstract: To investigate the clinical characteristics and outcomes of obstetric patients requiring intensive care unit (ICU) admission in a tertiary hospital. Methods: We retrospectively analyzed the clinical data of all pregnant/postpartum patients admitted to a tertiary ICU from January 2014 to December 2018. Result: One hundred and thirty-three obstetric patients were analyzed. Most patients (114, 85.7%) were admitted postpartum, and 57.9% (n = 77) of ICU admissions were from obstetric causes. The most common obstetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…15 Qureshi et al also concluded that MAP accounted for one third of ICU admissions because of extensive blood loss. 3 In a Chinese study by Zhang M et al 13 16 cases of ICU admission were due to placenta increta. Their study was over four years and analyzed one hundred and thirty three patients needing ICU admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Qureshi et al also concluded that MAP accounted for one third of ICU admissions because of extensive blood loss. 3 In a Chinese study by Zhang M et al 13 16 cases of ICU admission were due to placenta increta. Their study was over four years and analyzed one hundred and thirty three patients needing ICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac diseases were the cause of admission to ICU in 12% cases in a study conducted in China. 13 Improvement in medical technology has increased the survival of patients with congenital heart diseases. However, the physiological burden of pregnancy can unmask the compromised heart function in certain cases especially if they have not received proper preconception and antenatal care.…”
Section: Discussionmentioning
confidence: 99%